An ultra-wideband carbon / boron-doped high entropy alloy absorbing material and a preparation method thereof
High-entropy alloys are prepared by vacuum suspension smelting and vacuum air atomization ingots, and doping a small amount of C or B elements through sheeting treatment and stress annealing, which solves the problems of narrow frequency bands and complex preparation processes of existing high-entropy alloy absorbing materials, and realizes the efficient preparation and excellent absorption performance of ultra-wideband carbon/boron doped high-entropy alloy absorbing materials.
Patent Information
- Application Number
- CN202411796113.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The effective absorbing frequency bands of existing high-entropy alloy absorbing materials are usually narrow, which is difficult to meet the application requirements in a wider frequency band range. At the same time, the preparation process is complex, time-consuming, low efficiency, and difficult to produce in industrialized production.
High-entropy alloys are prepared by vacuum suspension smelting and vacuum air atomization ingots. Through sheeting treatment and stress annealing, the absorbance and production efficiency of the alloy are improved, and a small amount of C or B elements are doped to increase lattice distortion and improve the absorption performance.
The preparation of ultra-wideband carbon/boron doped high-entropy alloy absorbing materials has been realized, with the effective absorbing frequency band not less than 8.9GHz, the reflection loss value is not greater than -47.3dB, and the impedance matching and corrosion resistance of the material have been significantly improved, making it suitable for applications in wider bands.
Smart Images

Figure CN119287262B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding absorbing materials, and specifically relates to an ultra-wideband carbon / boron doped high entropy alloy absorbing material and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, especially 5G communication technology and aviation radar technology, the problem of electromagnetic pollution has become increasingly prominent. Electromagnetic wave absorbing materials (absorbent materials for short) can fundamentally resist and eliminate the harm of electromagnetic waves. Therefore, the development of absorbing materials with excellent performance has become a hot topic in current research.
[0003] As the service conditions of absorbing materials become more and more demanding, they are not only required to have the four characteristics of "thin", "light", "wide" and "strong", but also to have excellent corrosion resistance and high temperature oxidation resistance. Therefore, traditional absorbing materials such as carbonyl iron and ferrite are difficult to meet the current requirements. The existing alloy-type electromagnetic wave absorbers have high conductivity, the dielectric constant increases significantly after lamination, and the impedance mismatch reduces the absorbing performance of the material, which does not meet the use requirements.
[0004] High entropy alloys have become a new type of absorbing material due to their good mechanical properties, excellent soft magnetic properties, corrosion resistance, wear resistance, and oxidation resistance. High entropy alloys can improve their absorbing properties through a variety of control methods such as adjusting the type and concentration of the main elements, adding trace elements, and compounding with other materials. At present, people have obtained strong electromagnetic wave absorption properties in FeCoNi-based and FeNiCr-based high entropy alloys. For example, the invention patent with application number 202111466279.9 discloses a high entropy alloy absorbing material of FeNiCrAl with a reflection loss as low as -60.9dB. However, the effective absorbing frequency band of the high entropy alloys reported so far is usually narrow (below 7GHz), which is difficult to meet the application requirements in a wider frequency band. In addition, the current high entropy alloy absorbing materials are mainly prepared by high-energy ball milling of metal element powders, which has a low degree of alloying, is time-consuming, and has low efficiency, making it difficult to produce industrially.
[0005] Therefore, there is a need for an ultra-wideband carbon / boron-doped high entropy alloy absorbing material and a preparation method thereof. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing an ultra-wideband carbon / boron-doped high-entropy alloy absorbing material in view of the deficiencies of the above-mentioned prior art. The method first performs vacuum suspension melting to prepare an ingot, and then vacuum gas atomization ingots are used to batch prepare high-entropy alloys with a high degree of alloying for vacuum suspension melting, thereby reducing costs and improving production efficiency. The obtained carbon / boron-doped high-entropy alloy spherical powder is subjected to flaking treatment, and shape anisotropy is introduced to enable the soft magnetic high entropy to break through the Snoek limit at high frequency, thereby improving the absorbing performance. Through stress relief annealing heat treatment, the internal stress in the powder after ball milling is reduced, the impedance matching of the absorbing material is improved, and the absorbing performance of the material is further improved, thereby obtaining an ultra-wideband carbon / boron-doped high-entropy alloy absorbing material.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: an ultra-wideband carbon / boron doped high entropy alloy absorbing material, characterized in that the absorbing material is based on the FeCoNi medium entropy alloy, adjusting Fe and Ni elements, adding Si and Al elements, and doping a small amount of C or B elements, and the specific composition of the absorbing material is (Fe a Co b Si c Al d Ni e ) 100-x M x , where M represents C or B element, and a, b, c, d, e, and x represent the numerical values of the atomic percentages of the corresponding elements.
[0008] The above-mentioned ultra-wideband carbon / boron doped high entropy alloy absorbing material is characterized in that the (Fe a Co b Si c Al d Ni e ) 100-x M x Here a:b:c:d:e:x is 35~49:15~25:10~20:5~15:1~5:0.1~1, and a+b+c+d+e=100.
[0009] The absorbing material of the present invention is based on the FeCoNi medium entropy alloy, increases the Fe content with lower cost and adds the Si content with lower cost, reduces the Ni content with higher cost, reduces the alloy cost, adds the Al element to improve the corrosion resistance and oxidation resistance of the alloy, and dopes a small amount of C element or B element to increase lattice distortion, improve absorbing performance and corrosion resistance, reduce the electrical conductivity of the alloy, improve the impedance matching of the alloy, and finally improve the absorbing performance of the alloy, so as to obtain an ultra-wideband carbon / boron doped high entropy alloy absorbing material.
[0010] The above-mentioned ultra-wideband carbon / boron doped high entropy alloy absorbing material is characterized in that the effective absorbing frequency band of the absorbing material is not less than 8.9 GHz, and the minimum reflection loss value is not greater than -47.3 dB.
[0011] In addition, the present invention also provides a method for preparing an ultra-wideband carbon / boron doped high entropy alloy absorbing material, characterized in that the method comprises the following steps:
[0012] Step 1, high entropy alloy smelting: Fe, Co, Si, Al, Ni single-substance blocks and C or B single-substance particles are mixed, and then vacuum suspension smelting is performed and the surface oxide scale is removed to obtain a carbon / boron doped high entropy alloy ingot;
[0013] Step 2: preparing high entropy alloy spherical powder: vacuum gas atomizing the carbon / boron doped high entropy alloy ingot obtained in step 1, and then sieving to obtain carbon / boron doped high entropy alloy spherical powder;
[0014] Step 3, flaking treatment: the carbon / boron doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill for flaking treatment, and finally dried to obtain carbon / boron doped high entropy alloy flaked powder;
[0015] Step 4: stress relief annealing: the carbon / boron doped high entropy alloy flaked powder obtained in step 3 is placed in a tube furnace and subjected to heat treatment in an inert atmosphere to obtain a flaky ultra-wideband carbon / boron doped high entropy alloy absorbing material.
[0016] The present invention first prepares a carbon / boron doped high entropy alloy ingot by vacuum suspension smelting, and then vacuum gas atomization powdering is performed to obtain a spherical or quasi-spherical carbon / boron doped high entropy alloy spherical powder with a high alloying degree and stable performance. Compared with a high entropy alloy powder obtained by high-energy ball milling of a metal single substance powder, the high entropy alloy spherical powder has a simpler preparation process, higher efficiency, and can be mass-produced. The prepared carbon / boron doped high entropy alloy spherical powder is placed in a stainless steel ball milling tank for ball milling flaking. Unlike the previous use of ethanol as a control agent, the present invention uses weakly polar cyclohexane as a control agent in the flaking process. The control agent makes the flaking process faster, shortens the ball milling time, and improves the production efficiency. In addition, the carbon / boron doped high entropy alloy flaked powder obtained by using cyclohexane has a better flaked structure than the flaked powder obtained by adding anhydrous ethanol. Finally, the carbon / boron doped high entropy alloy flaked powder is placed in a tubular furnace for stress relief annealing, heated and kept warm for a certain period of time under the protection of inert gas to remove the internal stress in the ball milling process, and further aggravate the lattice distortion and increase the dipole generation, introduce a variety of loss mechanisms, improve the effective absorption bandwidth, and obtain an ultra-wideband carbon / boron doped high entropy alloy absorbing material.
[0017] In the present invention, the surface oxide scale is removed to improve the purity of the alloy, which is beneficial to the subsequent preparation of high-purity high-entropy alloy spherical powder.
[0018] The above method is characterized in that the mass purity of the Fe, Co, Si, Al, Ni single-substance blocks and C or B single-substance particles in step 1 is not less than 99.5%. The present invention uses raw materials with lower purity to significantly reduce the cost of raw materials.
[0019] The above method is characterized in that the vacuum degree in the vacuum suspension melting in step 1 is less than 5×10 -3 Pa, the smelting temperature is 1550℃~1650℃, the holding time after the raw material is melted is 5min~25min, and the melting is turned over for more than 4 times. The present invention adopts a lower vacuum degree to avoid oxidation of the raw material during the melting process, selects a higher melting temperature to avoid uneven composition due to insufficient melting of carbon particles, and selects a shorter holding time to avoid volatilization of aluminum elements caused by long-term high temperature insulation. By turning over and melting 4 times, the composition of the carbon / boron doped high entropy alloy ingot is more uniform.
[0020] The above method is characterized in that the temperature of the vacuum gas atomization powder making in step 2 is 1500°C to 1600°C, and the vacuum degree is less than 5×10 -3Pa, the particle size of the spherical powder is less than 15 μm. The present invention ensures that the alloy is not oxidized during the vacuum gas atomization powder making process by controlling the vacuum degree, and controls the temperature of the vacuum gas atomization powder making process to completely melt the alloy and ensure that the gas atomization process can be successfully completed. The vacuum gas atomization powder making process can obtain spherical powders of different particle sizes, and through screening, spherical powders with a particle size of less than 15 μm are screened out for subsequent experiments.
[0021] The above method is characterized in that the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm in step 3 is 2:7:1, the ball-to-material ratio in the flaking process is 20-40:1, the rotation speed is 400 r / min-550 r / min, and the time is 6h-18h. The present invention uses stainless steel grinding balls with different diameter ratios to act on spherical powders with different particle size ranges, adopts a higher ball-to-material ratio to make the flaking process more complete, and adopts a higher rotation speed and a shorter time to improve the efficiency of flaking.
[0022] It should be noted that, in the process of flaking, the present invention pauses for 5 minutes after each 30 minutes of ball milling. The intermittent process is adopted to avoid excessive temperature in the ball mill jar caused by continuous flaking, thereby causing oxidation of the powder.
[0023] The above method is characterized in that the heating rate of the heat treatment in step 4 is 10°C / min, the temperature is 400°C~600°C, the time is 30min~120min, the inert atmosphere is argon, and the heat treatment is cooled with the furnace after completion. The present invention effectively removes the internal stress of the sheet-like ultra-wideband carbon / boron-doped high-entropy alloy absorbing material by controlling the parameters of the heat treatment, aggravates the lattice distortion and increases the dipole generation, introduces a variety of loss mechanisms, and improves the effective absorption bandwidth of the ultra-wideband carbon / boron-doped high-entropy alloy absorbing material.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention increases the Fe content with lower cost and reduces the Ni content with higher cost on the basis of FeCoNi medium entropy alloy, and simultaneously adds Si and Al to prepare Fe a Co b Si c Al d Ni e High entropy alloy, and then doped with a small amount of non-metallic C and B elements as interstitial atoms to increase lattice distortion, improve absorbing performance and corrosion resistance, and obtain ultra-wideband carbon / boron doped high entropy alloy absorbing material. The obtained ultra-wideband carbon / boron doped carbon / boron high entropy alloy absorbing material can solve the industry problem that existing absorbing materials cannot have strong absorption, wide absorption frequency band, excellent corrosion resistance and oxidation resistance, and lay the foundation for the industrialization of alloy-type absorbing materials.
[0026] 2. The present invention uses weakly polar cyclohexane as a process control agent, which is more conducive to flaking the carbon / boron-doped high-entropy alloy spherical powder with strong internal stress, ensuring that the final ultra-wideband carbon / boron-doped high-entropy alloy absorbing material has a uniform flaky structure. The real and imaginary parts of the dielectric constant of the carbon / boron-doped high-entropy alloy after flaking are significantly improved, so that its absorbing ability and loss ability in the electric field are significantly improved, the impedance matching is improved, and the absorbing performance is improved.
[0027] 3. The present invention adopts a vacuum gas atomization method to prepare multi-component alloys in large quantities, and then adopts a preparation process of flaking treatment combined with stress relief annealing, which is conducive to obtaining flaked carbon / boron-doped high-entropy alloy spherical powder, so that the alloy powder has anisotropy in microstructure, which can break through the Snoke limit and achieve a higher magnetic permeability, thereby improving the material's wave absorbing performance, so that the material can simultaneously meet the "strong" absorption requirements of the wave absorbing material, thereby further broadening its application field.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a microstructure morphology diagram of the spherical powder prepared in Example 1 of the present invention.
[0030] Figure 2 This is a microstructure morphology diagram of the flaked powder prepared in Example 1 of the present invention.
[0031] Figure 3 This is a reflection loss-frequency diagram of the ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in Example 1 of the present invention when the thickness is 1.9 mm.
[0032] Figure 4 This is a reflection loss-frequency diagram of the ultra-wideband carbon-doped high entropy alloy absorbing material prepared in Example 1 of the present invention at different thicknesses.
[0033] Figure 5 This is a reflection loss-frequency diagram of the absorbing material prepared in Comparative Example 1 of the present invention when the thickness is 1.7 mm.
[0034] Figure 6 This is a reflection loss-frequency diagram of the absorbing material prepared in Comparative Example 1 of the present invention at different thicknesses.
[0035] Figure 7 This is a reflection loss-frequency diagram of the ultra-wideband boron-doped high entropy alloy absorbing material prepared in Example 2 of the present invention when the thickness is 2.0 mm.
[0036] Figure 8This is a reflection loss-frequency diagram of the ultra-wideband boron-doped high entropy alloy absorbing material prepared in Example 2 of the present invention at different thicknesses. DETAILED DESCRIPTION
[0037] Example 1
[0038] The molecular formula of the ultra-wideband carbon-doped high entropy alloy absorbing material of this embodiment is (Fe 49 Co 25 Si 10 Al 15 Ni1) 99 C1.
[0039] This embodiment includes the following steps:
[0040] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 49 Co 25 Si 10 Al 15 Ni1) 99 C1 is used for batching, and Fe, Co, Si, Al, Ni single-substance blocks and C single-substance particles with a mass purity of not less than 99.5% and a mass purity of not less than 99.5% are weighed, and then mixed and put into a vacuum suspension melting equipment, and then the vacuum degree is 3×10 -3 Pa, the temperature is 1550℃, the raw material is kept warm for 20min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a carbon-doped high entropy alloy ingot;
[0041] Step 2: Preparation of high entropy alloy spherical powder: The carbon-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 2×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1500°C, and then sieving to obtain carbon-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0042] Step 3, flaking treatment: the carbon-doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 40:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 400r / min, and the flaking treatment is carried out for 6 hours, and the ball milling is 30 minutes each time during the flaking treatment, and then paused for 5 minutes, and finally dried to obtain carbon-doped high entropy alloy flaked powder;
[0043] Step 4: stress relief annealing: the carbon-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 400°C at 10°C / min in an argon atmosphere, heat treated for 120 minutes, and then cooled in the furnace to obtain a flaky ultra-wideband carbon-doped high entropy alloy absorbing material.
[0044] The flaky ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the ultra-wideband carbon-doped high-entropy alloy was a single body-centered cubic structure. The microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the powder microstructure was thick flakes with a large width-to-thickness ratio. The electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material. The results showed that: Figure 3 and Figure 4 , Figure 3 and Figure 4 The horizontal axis represents the frequency of the electromagnetic wave, the vertical axis represents the reflection loss value, and the EAB in the figure represents the width of the effective absorbing frequency band. Figure 3 It can be seen that the ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment has an absorbing bandwidth of less than -10 dB up to 9.3 GHz in the range of 2 GHz to 18 GHz when the thickness is 1.9 mm. Figure 4 It can be seen that the ultra-wideband carbon-doped high-entropy alloy absorbing material has excellent absorbing performance, and the minimum reflection loss is -53.7dB, corresponding to a thickness of 2.6mm. It can be concluded that the best performance of the ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment is: when the thickness is 1.9mm, the effective absorbing frequency band is the widest, reaching 9.3GHz, and when the thickness is 2.6mm, the minimum reflection loss value is -53.7dB.
[0045] Figure 1 The microstructure morphology of the spherical powder prepared in this example is shown in FIG. Figure 1 It can be seen that the microscopic morphology of the spherical powder prepared in this embodiment is spherical or quasi-spherical, and the particle size is less than 15 μm.
[0046] Figure 2 The microstructure morphology of the flaked powder prepared in this example is shown in FIG. Figure 2 It can be seen that the flaked powder prepared in this embodiment is thick flakes, and the particle size of the flakes is 5 μm to 25 μm.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that the absorbing material is not doped with carbon element and the molecular formula is Fe 49 Co25 Si 10 Al 15 Ni1.
[0049] The absorbing material prepared in this comparative example was tested for electromagnetic parameters using a network vector analyzer combined with a coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material. The results showed that: Figure 6 , the EAB in the figure represents the width of the effective absorbing frequency band, from Figure 6 It can be seen that the minimum reflection loss of the absorbing material prepared in this comparative example is -48.3 dB, and the corresponding thickness is 3.7 mm.
[0050] By comparing Example 1 with Comparative Example 1, it can be seen that compared with the case where no carbon element is doped in Comparative Example 1, a small amount of carbon element is doped on the original composition of the high entropy alloy in Example 1, which improves the lattice distortion and internal stress of the high entropy alloy, improves impedance matching, and ultimately optimizes the absorbing performance of the material, reduces reflection loss (from -48.3 dB to -53.7 dB), significantly improves the effective absorption bandwidth (from 5.8 GHz to 9.3 GHz), and significantly reduces the thickness of the absorbing material (the thickness corresponding to the minimum reflection loss is reduced from 3.7 mm to 2.6 mm). In addition, carbon materials with lower doping density can also reduce the density of the material, meeting the concepts and requirements of "thin", "light", "wide" and "strong" required for absorbing materials. At the same time, the effect of a small amount of doped carbon elements on the corrosion resistance and oxidation resistance of the material is negligible.
[0051] Example 2
[0052] The molecular formula of the carbon-doped high entropy alloy absorbing material of this embodiment is (Fe 35 Co 25 Si 20 Al 15 Ni5) 99.9 C 0.1 .
[0053] This embodiment includes the following steps:
[0054] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 35 Co 15 Si 20 Al 15 Ni5) 99.9 C 0.1 The materials were weighed, and the corresponding masses of Fe, Co, Si, Al, Ni single-substance blocks and C single-substance particles with a mass purity of not less than 99.5% were mixed and placed in a vacuum suspension melting equipment, and then the vacuum degree was 2×10 -3Pa, the temperature is 1650℃, the raw material is kept warm for 5min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a carbon-doped high entropy alloy ingot;
[0055] Step 2: Preparation of high entropy alloy spherical powder: The carbon-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 3×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1600°C, and then sieving to obtain carbon-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0056] Step 3, flaking treatment: the carbon-doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 20:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 550r / min, and the flaking treatment is carried out for 18 hours. During the flaking treatment, each ball mill is milled for 30 minutes, and then paused for 5 minutes, and finally dried to obtain carbon-doped high entropy alloy flaked powder;
[0057] Step 4: stress relief annealing: the carbon-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 600°C at 10°C / min in an argon atmosphere, heat treated for 30 minutes, and then cooled in the furnace to obtain a flaky ultra-wideband carbon-doped high entropy alloy absorbing material.
[0058] The ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the phase structure of the alloy was a single body-centered cubic structure. The microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the powder microstructure was thick flakes with a large width-to-thickness ratio. The electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material. The results showed that: Figure 7 and Figure 8 , the EAB in the figure represents the width of the effective absorbing frequency band, from Figure 7 It can be seen from the figure that the ultra-wideband carbon-doped high entropy alloy absorbing material prepared in this embodiment has an absorbing bandwidth of 9.2 GHz below -10 dB in the range of 2 GHz to 18 GHz when the thickness is 2.0 mm. Figure 8It can be seen that the ultra-wideband carbon-doped high-entropy alloy absorbing material has excellent absorbing performance, and the minimum reflection loss is -47.3dB, corresponding to a thickness of 3.6mm. It can be concluded that the best performance of the ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment is: when the thickness is 2.0mm, the effective absorbing frequency band is the widest, reaching 9.2GHz, and when the thickness is 3.6mm, the minimum reflection loss value is -47.3dB.
[0059] Example 3
[0060] The molecular formula of the carbon-doped high entropy alloy absorbing material of this embodiment is (Fe 40 Co 25 Si 18 Al 13 Ni4) 99.5 C 0.5 .
[0061] This embodiment includes the following steps:
[0062] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 40 Co 25 Si 18 Al 13 Ni4) 99.5 C 0.5 The materials were weighed, and the corresponding masses of Fe, Co, Si, Al, Ni single-substance blocks and C single-substance particles with a mass purity of not less than 99.5% were mixed and placed in a vacuum suspension melting equipment, and then the vacuum degree was 2.6×10 -3 Pa, the temperature is 1620℃, the raw material is kept warm for 13min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a carbon-doped high-entropy alloy ingot;
[0063] Step 2: Preparation of high entropy alloy spherical powder: The carbon-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 3.2×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1550°C, and then sieving to obtain carbon-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0064] Step 3, flaking treatment: the carbon-doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 32:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 480r / min, and the flaking treatment is carried out for 10 hours. During the flaking treatment, each ball mill is milled for 30 minutes, and then paused for 5 minutes, and finally dried to obtain carbon-doped high entropy alloy flaked powder;
[0065] Step 4: stress relief annealing: the carbon-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 550°C at 10°C / min in an argon atmosphere, heat treated for 45 minutes, and then cooled in the furnace to obtain a flaky ultra-wideband carbon-doped high entropy alloy absorbing material.
[0066] The sheet-like ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the phase structure of the alloy was a single body-centered cubic structure. The microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the microstructure of the powder was thick flakes with a large width-to-thickness ratio. The electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material. The results showed that the ultra-wideband carbon-doped high-entropy alloy absorbing material prepared in this embodiment had the widest effective absorbing frequency band of 8.9 GHz when the thickness was 1.7 mm, and the minimum reflection loss value was -52.0 dB when the thickness was 2.9 mm.
[0067] Example 4
[0068] The molecular formula of the boron-doped high entropy alloy absorbing material of this embodiment is (Fe 48 Co 24 Si 19 Al5Ni4) 99 B1.
[0069] This embodiment includes the following steps:
[0070] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 48 Co 24 Si 19 Al5Ni4) 99 B1 is used for batching. The corresponding masses of Fe, Co, Si, Al, Ni single-substance blocks with a purity of not less than 99.5% and B single-substance particles are weighed and then mixed and placed in a vacuum suspension melting equipment. The vacuum degree is 3×10 -3 Pa, the temperature is 1600℃, the raw material is kept warm for 10min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a boron-doped high entropy alloy ingot;
[0071] Step 2: Preparation of high entropy alloy spherical powder: The boron-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 2.5×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1550°C, and then sieving to obtain boron-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0072] Step 3, flaking treatment: the boron-doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 30:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 500r / min, and the flaking treatment is carried out for 12 hours. During the flaking treatment, each ball mill is milled for 30 minutes, and then paused for 5 minutes, and finally dried to obtain a boron-doped high entropy alloy flaked powder;
[0073] Step 4, stress relief annealing: the boron-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 500°C at 10°C / min in an argon atmosphere, heat treated for 60 minutes, and then cooled with the furnace to obtain a flaky ultra-wideband boron-doped high entropy alloy absorbing material.
[0074] The sheet-like ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the phase structure of the alloy was a single body-centered cubic structure; the microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the powder microstructure was thick flakes with a large width-to-thickness ratio; the electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material, and the results showed that the ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment had the widest effective absorbing frequency band of 9.1 GHz when the thickness was 1.8 mm, and the minimum reflection loss value was -51.2 dB when the thickness was 3.0 mm.
[0075] Example 5
[0076] The molecular formula of the boron-doped high entropy alloy absorbing material of this embodiment is (Fe 48 Co 15 Si 19 Al 14 Ni4) 99.9 B 0.1 .
[0077] This embodiment includes the following steps:
[0078] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 48 Co 15 Si 19 Al 14 Ni4) 99.9 B 0.1The materials were weighed, and the corresponding masses of Fe, Co, Si, Al, Ni single-substance blocks and B single-substance particles with a mass purity of not less than 99.5% were mixed and placed in a vacuum suspension melting equipment, and then the vacuum degree was 2.8×10 -3 Pa, the temperature is 1620℃, the raw material is kept warm for 15min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a boron-doped high entropy alloy ingot;
[0079] Step 2: Preparation of high entropy alloy spherical powder: The boron-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 2×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1580°C, and then sieving to obtain boron-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0080] Step 3, flaking treatment: the boron-doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 24:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 520r / min, and the flaking treatment is carried out for 14 hours. During the flaking treatment, each ball mill is milled for 30 minutes, and then paused for 5 minutes, and finally dried to obtain a boron-doped high entropy alloy flaked powder;
[0081] Step 4: stress relief annealing: the boron-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 530°C at 10°C / min in an argon atmosphere, heat treated for 50 minutes, and then cooled with the furnace to obtain a flaky ultra-wideband boron-doped high entropy alloy absorbing material.
[0082] The sheet-like ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the phase structure of the alloy was a single body-centered cubic structure; the microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the powder microstructure was thick flakes with a large width-to-thickness ratio; the electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material, and the results showed that the ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment had the widest effective absorbing frequency band of 9.0 GHz when the thickness was 1.6 mm, and the minimum reflection loss value was -52.3 dB when the thickness was 3.1 mm.
[0083] Example 6
[0084] The molecular formula of the boron-doped high entropy alloy absorbing material of this embodiment is (Fe 39 Co 24 Si 19 Al 13 Ni5) 99.4 B 0.6 .
[0085] This embodiment includes the following steps:
[0086] Step 1: High entropy alloy smelting: According to the molecular formula (Fe 39 Co 24 Si 19 Al 13 Ni5) 99.4 B 0.6 The materials were weighed, and the corresponding masses of Fe, Co, Si, Al, Ni single-substance blocks and B single-substance particles with a mass purity of not less than 99.5% were mixed and placed in a vacuum suspension melting equipment, and then the vacuum degree was 3.5×10 -3 Pa, the temperature is 1590℃, the raw material is kept warm for 25min after melting, and the vacuum suspension melting is performed 4 times, and finally the surface oxide scale is removed to obtain a boron-doped high entropy alloy ingot;
[0087] Step 2: Preparation of high entropy alloy spherical powder: The boron-doped high entropy alloy ingot obtained in step 1 is placed in a vacuum gas atomization device with a vacuum degree of 2.3×10 -3 Pa, vacuum gas atomization powdering at a temperature of 1560°C, and then sieving to obtain boron-doped high entropy alloy spherical powder with a particle size of less than 15 μm;
[0088] Step 3, flaking treatment: the boron-doped high entropy alloy spherical powder obtained in step 2 is loaded into a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, the mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm is 2:7:1, and the ball-to-material ratio is 36:1, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill, and the rotation speed is 470r / min, and the flaking treatment is carried out for 8h, and the ball milling is 30min each time during the flaking treatment, and then paused for 5min, and finally dried to obtain the boron-doped high entropy alloy flaked powder;
[0089] Step 4, stress relief annealing: the boron-doped high entropy alloy flaked powder obtained in step 3 is placed in a tubular furnace, the temperature is raised to 480°C at 10°C / min in an argon atmosphere, heat treated for 90 minutes, and then cooled with the furnace to obtain a flaky ultra-wideband boron-doped high entropy alloy absorbing material.
[0090] The sheet-like ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment was subjected to phase structure analysis, microstructure analysis and absorbing performance test. The phase structure of the absorbing material was analyzed by X-ray diffractometer (XRD), and the results showed that the alloy phase structure was a single body-centered cubic structure; the microstructure of the absorbing material was observed by tungsten filament scanning electron microscope, and the results showed that the powder microstructure was thick flakes with a large width-to-thickness ratio; the electromagnetic parameters were tested by network vector analyzer combined with coaxial method (powder: paraffin = 7:3) to obtain the absorbing performance of the absorbing material, and the results showed that the ultra-wideband boron-doped high-entropy alloy absorbing material prepared in this embodiment had the widest effective absorbing frequency band of 9.1 GHz when the thickness was 1.8 mm, and the minimum reflection loss value was -53.0 dB when the thickness was 3.3 mm.
[0091] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An ultra-wideband carbon / boron doped high entropy alloy absorbing material, characterized in that: The absorbing material is prepared by adjusting Fe and Ni elements on the basis of FeCoNi medium entropy alloy, adding Si and Al elements, and doping a small amount of C or B elements. The specific composition of the absorbing material is (Fe a Co b Si c Al d Ni e ) 100-x M x , where M represents C or B element, a, b, c, d, e, x represent the atomic percentage of the corresponding element, and the (Fe a Co b Si c Al d Ni e ) 100-x M x a:b:c:d:e:x is 35~49:15~25:10~20:5~15:1~5:0.1~1, and a+b+c+d+e=100; The preparation method of the wave absorbing material comprises the following steps: Step 1, high entropy alloy smelting: Fe, Co, Si, Al, Ni single-substance blocks and C or B single-substance particles are mixed, and then vacuum suspension smelting is performed and the surface oxide scale is removed to obtain a carbon / boron doped high entropy alloy ingot; Step 2: preparing high entropy alloy spherical powder: vacuum gas atomizing the carbon / boron doped high entropy alloy ingot obtained in step 1, and then sieving to obtain carbon / boron doped high entropy alloy spherical powder; Step 3, flaking treatment: the carbon / boron doped high entropy alloy spherical powder obtained in step 2 is placed in a stainless steel vacuum ball mill, and stainless steel grinding balls and cyclohexane are added, and then the vacuum and argon filling are repeated several times and then sealed, and then placed in a planetary ball mill for flaking treatment, and finally dried to obtain carbon / boron doped high entropy alloy flaked powder; Step 4: stress relief annealing: the carbon / boron doped high entropy alloy flaked powder obtained in step 3 is placed in a tube furnace and subjected to heat treatment in an inert atmosphere to obtain a flaky ultra-wideband carbon / boron doped high entropy alloy absorbing material.
2. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The effective absorbing frequency band of the absorbing material is not less than 8.9 GHz, and the minimum reflection loss value is not greater than -47.3 dB.
3. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The mass purity of the Fe, Co, Si, Al, Ni single-substance blocks and C or B single-substance particles described in step 1 is not less than 99.5%.
4. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The vacuum degree in the vacuum suspension melting in step 1 is less than 5×10 -3 Pa, the smelting temperature is 1550℃~1650℃, the insulation time after the raw materials are melted is 5min~25min, and the smelting is turned over more than 4 times.
5. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The temperature of the vacuum gas atomization powder making in step 2 is 1500°C to 1600°C, and the vacuum degree is less than 5×10 -3 Pa, the particle size of the spherical powder is less than 15 μm.
6. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The mass ratio of the stainless steel grinding balls with diameters of 10 mm, 6 mm and 3 mm in step 3 is 2:7:1, the ball-to-material ratio in the flaking treatment is 20-40:1, the rotation speed is 400 r / min-550 r / min, and the time is 6 h-18 h.
7. The ultra-wideband carbon / boron doped high entropy alloy absorbing material according to claim 1, characterized in that: The heating rate of the heat treatment in step 4 is 10°C / min, the temperature is 400°C~600°C, the time is 30min~120min, the inert atmosphere is argon, and the heat treatment is cooled in the furnace after completion.
Citation Information
Patent Citations
A high-entropy alloy microwave absorbing material with a reflection loss of -60.9 dB and its preparation method.
CN113862545B
FeSiBAlNiCo block high-entropy alloy and preparation method thereof
CN105861909A